The physics of rock failure and earthquakes - Onaka, Michiyasu, 1940- (Cambridge : Cambridge University Press, 2013)
'Physical modelling of earthquake generation processes is essential to further our understanding of seismic hazard. However, the scale-dependent nature of earthquake rupture processes is further complicated by the heterogeneous nature of the crust. Despite significant advances in the understanding of earthquake generation processes, and the derivation of underlying physical laws, controversy remains regarding what the constitutive law for earthquake ruptures ought to be, and how it should be formulated. It is extremely difficult to obtain field data to define physical properties along a fault during a rupture event, at sufficiently high spatial and temporal resolution to resolve the controversy. Instead, laboratory experiments offer a means of obtaining high-resolution measurements that allow the physical nature of shear rupture processes to be deduced. This important new book is written using consistent notation, providing a deeper understanding of earthquake processes from nucleation to their dynamic propagation. Its key focus is a deductive approach based on laboratory-derived physical laws and formulae, such as a unifying constitutive law, a constitutive scaling law, and a physical model of shear rupture nucleation. Topics covered include: the fundamentals of rock failure physics, earthquake generation processes, physical scale dependence, and large-earthquake generation cycles and their seismic activity'--
Introduction -- Fundamentals of rock failure physics -- Laboratory-derived constitutive relations for shear failure -- Constitutive laws for earthquake ruptures -- Earthquake generation processes -- Physical scale-dependence -- Large earthquake generation cycles and accompanying seismic activity.
Includes bibliographical references and index.
Keywords: Seismology; Rock mechanics; Earthquakes